Transfer of Function of Wakaf Land According To Law No. 41 of 2004 (Case Study In Medan City) - Muhammad Yunus (AT-TAFAHUM: Journal of Law, 2018)
This study examines the legal concept of waqf, the requirements and pillars of waqf, and the transfer of function of waqf land in Medan City from the perspective of Islamic law and Indonesian positive law, particularly Law Number 41 of 2004 concerning Waqf. Waqf is an Islamic legal institution aimed at maintaining the principal value of assets while utilizing their benefits for religious and public welfare purposes. Differences in scholarly opinions regarding waqf demonstrate the flexibility of interpretation concerning ownership, duration, and management of waqf assets. Indonesian regulations have provided legal certainty through Law No. 41 of 2004, Government Regulation No. 42 of 2006, and the Compilation of Islamic Law. This research applies an empirical juridical method through analysis of legislation, legal documents, and cases of waqf land conversion in Medan City, including Toyyibah Mosque, Raudhatul Islam Mosque, Al-Falah Mosque, and Amal Silaturrahim Mosque. The findings indicate that conversion of waqf land is legally permissible only for public interest purposes, provided it complies with spatial planning regulations, receives approval from the Minister of Religion and the Indonesian Waqf Board (BWI), and ensures replacement assets possess equal or greater value. The study also finds that not all conversions comply with applicable laws, as seen in the Toyyibah Mosque case, where conversion relied solely on a local religious decree without fulfilling statutory procedures. Therefore, strict supervision and compliance with legal mechanisms are essential to preserve the sanctity, continuity, and social function of waqf assets for public welfare and sustainable religious development.